A tentative semantic map of depictives and other secondary participant-oriented predicates in the Lithuanian language - Čižik-Prokaševa, Veslava (Lietuvių kalba, 2011)
The article sets out to analyse the similarities and differences of free secondary predicates (predicative adjuncts) in the Lithuanian language and secondary predicates in other languages. The study has been carried out relying on the universal semantic map for participant-oriented modifiers drawn by N. P. Himmelmann and E. Schultze-Berndt (2005) and on the basis of the elements of its composition. The analysis has demonstrated that the majority of Lithuanian language modifiers which have usually been analysed as circumstantials, i.e. as event-oriented modifiers, are in fact also participant-oriented. Their semantic link with the participant is reflected not only by the secondary predicates of physical, mental or emotional condition, function, role, association, collective or life stage but also by those of manner, concomitance, distributivity, time and even location and atmospheric condition. As a result, a tentative semantic map of participant-oriented modifiers in the Lithuanian language has been composed and it is provided in the article. This map is different from the universal map of Himmelmann and Schultze-Berndt because of the specificity of the Lithuanian language (secondary predicates of time, collective, distributivity, order, frequency and emphatic pronoun in the map of the Lithuanian language have fallen into different places; the denotation of location of event has been eliminated) and because of different theoretical principles selected for this study (the denotations of comparison and benefactive / malefactive are eliminated, circumstantial secondary predicates are added). With respect to the possible denotations of free secondary predicates in different languages of the word as proposed by Himmelmann and Schultze-Berndt, the Lithuanian language only lacks those of comparison, benefactive / malefactive and location of event; however, it is possible to distinguish additional categories of causal, temporal, conditional and concessive circumstantials. On the basis of the investigation, the following tentative semantic map of participant-oriented modifiers in the Lithuanian language has been drawn.
Keywords: none